Parent reports of children's parasocial relationships with conversational agents: Trusted voices in children's lives. Issue 4 (21st June 2021) - Hoffman, Anna; Owen, Diana; Calvert, Sandra L.
Abstract: With the rise of smart devices in the 21st century, children are increasingly engaged in socially contingent interactions with conversational agents such as Alexa, Google Assistant, and Siri. Using an online parent survey, young children's verbal interactions (parasocial interactions) and emotional relationships (parasocial relationships) with conversational agents were examined in a naturalistic study. A total of 92 parents responded to the survey, 70 of whom qualified because they had a conversational agent. Exploratory and confirmatory factor analyses of emotional parasocial relationships with conversational agents in a subset of this sample ( n = 58, m child age = 5.54 years, age range 3–10, 33 females) revealed three dimensions: attachment, personification, and social realism. These dimensions are consistent with children's parasocial relationships with media characters. The relation between parasocial verbal interactions and emotional parasocial relationships with conversational agents was bidirectional. The results indicate that children develop close emotional ties with artificial beings, treating them as human‐like entities with feelings and for whom they have feelings. Implications for interactions with artificial life as children's trusted social partners are considered.